Cultural Capital and Educational Performance of Brahman/Chhetri Students - Simkhada, Sharad Chandra (Molung Educational Frontier, 2020)
Why Brahman/Chhetri students are high achievers in secondary education in Nepal is rarely analyzed. For their educational success, people attribute to their cultural capital. A qualitative method was employed to assess whether the assumption is valid or not. In the course of assessment, researcher generated information from secondary and primary sources and analyzed them. The findings show that the Brahman/Chhetris are rich in cultural capital, which is instrumental for their better performance in formal education. However, empirical evidence has led the researcher that the argument is valid partly. Due to globalization combined with other factors such as class, education, and growing cultural exchange, the influence of cultural capital to their educational achievement has been found weak. Therefore, the stereotypical generalization is not necessarily true at present, among the research participants.